Integrated Co-functional Network Analysis on the Resistance and Virulence Features in Acinetobacter baumannii - Xie, Ruiqiang; Shao, Ningyi; Zheng, Jun (Frontiers in Microbiology, 2020)
Acinetobacter baumannii is one of the most troublesome bacterial pathogens that pose a major public health threat due to its rapidly increasing drug resistance property. It was recently also recognized as an emerging fish pathogen. Understanding the mechanism of antibiotic resistance development and pathogenesis will aid our battle with the infections caused by A. baumannii. In this study, we constructed a co-functional network by integrating multiple sources of data from A. baumannii and then used the k-shell decomposition to analyze the co-functional network. We found that genes involving in basic cellular physiological function, including genes for antibiotic resistance, have high k shell value and locate in the internal layer of our network. In contrast, the non-essential genes, such as genes associate with virulence, tend to have a lower k shell value and locate in the external layer. This finding allows us to fish out the potential antibiotic resistance factors and virulence factors. In addition, we constructed an online platform ABviresDB (https://acba.shinyapps.io/ABviresDB/) for visualization of the network and features of each gene in A. baumannii. The network analysis in this study will not only aid the study on A. baumannii but also could be referenced for the research of antibiotic resistance and pathogenesis in other bacteria.